INNV-08. CASE REPORT OF AN OLDER GLIOBLASTOMA PATIENT SURVIVING MORE THAN 12 YEARS AFTER TREATMENT WITH CILENGITIDE IN ADDITION TO STANDARD THERAPY. (14th November 2022) - Alalami, Huda; Hu, Jethro; Fan, Xuemo; Bannykh, Serguei
Abstract: BACKGROUND: Glioblastoma is the most common malignant brain tumor. Less than 1% of patients survive longer than 10 years. Integrins are implicated in tumorigenesis due to their role in cell adhesion and intercellular communication. Cilengitide, a selective αvβ3, and αvβ5 integrin inhibitor, was studied for patients with glioblastoma. RESULTS: A 77-year-old woman was found to have a left temporoparietal MGMT methylated glioblastoma after presenting with visual field deficits in 2009. She underwent near gross total resection of the tumor. The tumor had retained expression of PTEN and MAPK. No mutations in IDH or ATRX were detected. Genetic testing revealed mutations in TERT promoter, TP53, SYNE1, NF1, PTEN, FBXW7, POLD1, ERG, and PRKDC. She was enrolled in the CENTRIC trial, a phase III clinical trial studying the addition of cilengitide to standard therapy for patients with newly diagnosed glioblastoma with methylated MGMT promoter. In 2013, the initial results of the study failed to meet the endpoint of prolonged overall survival and progression-free survival, therefore the study was halted. The patient received cilengitide through compassionate use until 2016. Surveillance brain MRI obtained every three shows no radiographic evidence of recurrence. CONCLUSION: Although it is known that methylated-MGMT promoter is one of the few positive prognostic factors in GBM, overall survival remains poor in older patients. This case highlights a rare clinical response to treatment in an older female who has survived more than 12 years without disease recurrence after receiving cilengitide in addition to standard therapy. Her outcome may have been influenced by the expression of PTEN and the methylation of MGMT, which are associated with improved outcomes. Although the development of cilengitide was halted for lack of efficacy, the existence of individual responders such as this patient suggests that further study of integrin inhibition for glioblastoma patients may be worth pursuing.